Subsystem of information interaction in the system of collecting medical statistical data - Alexander A. Lisnenko; Veronica A. Asmus; Timofey A. Asmus (RUDN Journal of Public Administration, 2025)
The purpose of the study is describing the configuration and topology of a message broker for asynchronous and reliable data transmission in the information interaction subsystem as part of the modernization of the system for collecting and processing medical statistical data. Information from regulatory and legal acts, federal law, as well as data on current research in the field of data transmission were used. Medical statistics is a branch of statistics that includes data on medicine, public health, and the activities of medical organizations. Medical statistics allow the most efficient allocation of limited health resources. The introduction of digital technologies contributes to the effective collection of medical statistics. As part of the digital transformation of the healthcare system, the process of collecting medical statistics is being optimized. One of the optimization tools is the introduction of electronic medical document management, where each document is presented in the form of a structured electronic medical document. An example of structuring an electronic document for medical statistics is documents structured in accordance with the international standard for the exchange of statistical data and metadata - Statistical data and metadata exchange. The main advantages of optimization are the ability to receive information in real time, the asynchrony of the messaging process and the ordering of the flow of medical data over time. To ensure the operation of the information system, it is necessary to configure the subsystem of information interaction between medical data sources and their processing centers. As such a subsystem, we suggest using an intermediary program for asynchronous message transmission. A program that implements the message broker design pattern. The study describes the advantages of the Apache Kafka message broker. The introduction of such a subsystem makes it possible to change the system of information interaction between administrative levels, so that the upper levels can directly receive the initial raw data from the lower levels. At the same time, the number of Apache Kafka clusters depends on the number of administrative units that medical institutions are assigned to.